A dynamic routing scheme for underwater acoustic sensor networks in submarine disaster applications - Jiang, Peng; Wang, Hao; Xiong, Zhiwen (Frontiers in Marine Science, 2024)
The ocean economy serves as a critical engine for the development of human society and economy, and its stable growth is of utmost importance. However, the frequent and unexpected occurrence of natural disasters such as Submarine disasters poses significant threats to human society, especially disasters related to wave phenomena like the Ekman current, which have particularly prominent impacts. Therefore, the present study proposes a dynamic routing scheme for underwater acoustic sensor networks. This scheme establishes a Cone-shaped distributed network, utilizing autonomous underwater vehicles (AUVs) to collect crucial data from nodes deployed on the seabed and transmit it through the underwater cone-shaped distributed sensor network. This approach significantly reduces the frequency of routing information exchange and energy consumption among acoustic sensors, effectively enhancing the economy and durability of the sensor network. Additionally, it adopts SLP (source location protection) technology to ensure the privacy of source locations. To validate the practicality and stability of this scheme, simulation experiments targeting the Ekman current were conducted in MATLAB. The experimental results demonstrate that the Cone-SLP network exhibits strong practicality and high stability in complex and variable submarine environments. This research not only provides a practical method for effectively monitoring submarine disasters but also offers valuable experience and significant reference value for other similar projects, playing a more crucial role in the sustainable development of the ocean economy.